Case Report: Transient Increase of CMR T1 Mapping Indices in a Patient With COVID-19 mRNA Vaccine Induced Acute Myocarditis - Ansari, Uzair; Britsch, Simone; Rogowski, Sebastian; Duerschmied, Daniel; Papavassiliu, Theano (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute myocarditis is commonly associated with viral infections, including severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Myocarditis following mRNA COVID-19 vaccination has also been reported, however this is rare and usually resolves within days or weeks. We present a case of acute myocarditis reported after vaccination with mRNA-1273 COVID-19 vaccine (Moderna) diagnosed using cardiac magnetic resonance imaging (CMR). This report describes the utility of CMR in the diagnosis and follow-up of such patients using parameters which could suggest the clinical course of myocarditis. Case Summary: A 23- year-old male presented in the emergency department with complaints of chest pain radiating to the left arm following vaccination with the second dose of COVID-19 mRNA-1273 vaccine (Moderna). Patient’s history revealed an incidence of myocarditis in the past. CMR showed a mid-range left ventricular ejection fraction (38%) and subepicardial late gadolinium enhancement (LGE) in the inferolateral and apical myocardial segments with diffuse elevation of native T1 mapping relaxation times in all myocardial segments. The patient was admitted briefly in the intensive care unit and after a favorable clinical course was discharged from the hospital in stable condition. A follow-up CMR after 3 months revealed normalization of LVEF (57%) and native T1- times in most segments. Scarred myocardium reflecting chronic myocarditis continued to show elevated T1 times. Conclusions: Our patient presenting with acute myocarditis after recent COVID-19 mRNA vaccination reported a favourable clinical course. CMR revealed increased T1 mapping relaxation times diffusely spread across the myocardium and an impairment of the left ventricular function (LVEF) during the acute phase. However, the LVEF as well as the T1 times normalized at follow-up in all segments except for myocardium affected by chronic myocarditis.